Análisis biomecánico de la técnica de la marcha atlética en la longitud de pasos en deportistas - Pinoargote Anchundia, Pierina Dayana (2024)
The present research work called "biomechanical analysis of the art athletic march in the length of steps in athletes", responds to a quantitative research approach of correlational descriptive type, applied to a 4-in-out of the athletes of the athletic debt of the Silvanced Chief Cloudy deficiency of the Chimborazo (FDCH) and distributed in different categories, taking into account that much of the sample has sports experience in competitions in events nationally and internationally. As a method of research, biomechanical analysis was applied using parameters that characterize this discipline, such as the location of the center of gravity by phases, angular moment by phases, and stretch length. The results obtained allowed us to compare the variability of these parameters in the different categories, determining that about the location of the center of gravity, the values of the angular moments, and stretch length both right and left, there are differences concerning the sports experience and the anthropometric characteristics, in which the differences are minimal. There is no dependence on relation to the category and technique of the athlete. However, the execution speed per phase determines as a trend a maximum speed in the double support phase with leg, a way of greater speed of greater category. The research results are presented through graphic representations, tables and figures, and a descriptive analysis of the minimum, maximum, and median values with their respective standard deviations by applying for the SPSS program.